The Incorporation of Potassium Antimony Tartrate in Molybdenum Blue Method for the Automated Colorimetric Determination of Available Phosphorus in Soils - Tiong, S. M . I (1987)
The incorporation of potassium antimony tartrate (KSbOC 4H 40 j in molybdenum blueascorbic acid (Mo blue) method for phosphorus (P) determination of Bray & Kurtz No.2 soil extract was studied. Results obtained by this method are in close agreement with those by Fogg and Wilkinson and Stannous Chloride manual methods.